Islamic Character Education Strategies for Preventing Bullying: A Qualitative Case Study at Madrasah Aliyah Baitul Arqam, Aceh Besar - Rosnidarwati, Rosnidarwati; Sirajuddin, Sirajuddin; Yusliani, Hamdi; Irhamna, Irhamna (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: This study examines Islamic character education strategies implemented to prevent bullying behavior at Madrasah Aliyah Baitul Arqam, Aceh Besar. Methodology: A qualitative case study design was employed involving 15 informants, including the school principal, Islamic Religious Education teachers, guidance and counseling teachers, and students. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using descriptive qualitative techniques supported by triangulation. Main Findings: The findings indicate significant qualitative outcomes, including positive behavioral changes among students, increased awareness of the psychological and social impacts of bullying, stronger internalization of Islamic moral values, and a noticeable reduction in bullying incidents. Islamic character education is systematically implemented through teacher role modeling, religious habituation, moral instruction, and Islamic-based disciplinary practices. These mechanisms cultivate empathy, self-regulation, mutual respect, and a sense of safety within the school environment. Novelty/Originality of this study: This research introduces an integrative Islamic preventive model that combines character education and Islamic conflict resolution such as nasihah, musyawarah, and spiritual guidance as an effective framework for bullying prevention in Islamic secondary education.